Curative effect analysis of robot-assisted drainage surgery in treatment of spontaneous hypertensive brainstem hemorrhage - Tang, Zhiji; Huang, Weilong; Chen, Qiqi; Guo, Changgui; Zheng, Kuan; Wei, Wenjin; Jiang, Qiuhua; Yang, Ruijin (Frontiers in Neurology, 2024)
OBJECTIVE: Spontaneous hypertensive brainstem hemorrhage (HBSH) is characterized by sudden onset, rapid progression and poor prognosis. There has been a growing tendency of surgical treatment for HBSH. This study aimed to investigate outcomes and potential factors associated with the prognosis of robot-assisted drainage surgery for HBSH treatment. METHODS: Patients with HBSH from July 2016 to March 2023 at a single neurosurgery center were included and divided into conservative group and surgical groups. Baseline and clinical data, radiographic characteristics, complications, and outcome evaluations were recorded and analyzed.RESULTS: A total of 125 patients, with 74 in the conservative group and 51 in the surgical group, were enrolled in the study. Mortality at 6 months was 59/74 (79.7%) in the conservative group and 9/51 (17.6%) in the surgical group.Twenty-four patients (47.1%) achieved favorable outcomes in the surgical group, whereas this rate in the conservative group was only 5.4% (4/74). There was a significant difference in NIHSS, GCS, and mRS at 6 months between surviving patients in the conservative and surgical groups. In prognostic analysis in the surgical subgroup, initial GCS score (5[IQR 4-7] vs. 3[IQR 3-4], P<0.001), , P<0.001), smoking history (45.8%(11/24) vs. 74.1%(20/27), P=0.039), hematoma volume (6.9 ], P=0.001), and hemorrhage location (P=0.001) were potential risk factors for poor 6-month prognosis after robot-assisted surgery for HBSH.Based on the results of this study, robot-assisted minimally invasive drainage of brain stem hematoma may significantly reduce mortality and improve prognosis. Surgery should be conducted for selected patients.